(untitled) (Research, Society and Development, 2023)
Patient discharge is defined as the patient’s departure from the hospital environment and involves care demands generated during hospitalization, such as the various drug adjustments that weaken the transfer of care to primary care, increasing the risk of Drug-Related Problems (DRPs). The pharmacist performs the prevention, detection and resolution of DRPs and positively influences the post-hospital care through his interventions, such as Medication Reconciliation (RM). The objective of this study was to identify references that demonstrate the importance of the pharmacist at the time of patient discharge and to elaborate a Standard Operating Procedure (SOP) based on the documents in order to guide the pharmaceutical conduct in the context of patient discharge and to produce didactic material that contributes to the pharmaceutical orientation inserted in a hospital institution. This is an integrative review using the PICO strategy for the guiding question, following the following descriptors: “patient discharge”, “pharmaceutical care”, “medication reconciliation” and “patient safety”. The results found in the articles demonstrate the importance of the pharmacist during hospital discharge, monitoring and avoiding DRPs, waiting for hospital readmissions and cost, providing patient safety. Thus, it is important that this professional is included in the discharge process, supervising the planning, monitoring the length of stay and ensuring the rational use of the medication.